An Optimization of the Adsorption Method for Methylene Blue Using Faujasite Zeolite-X Synthesized from Coal-Fly Ash Utilizing RSM Coupled with Central Composite Design Approach - Tirva, Divya; Sur, Dharmesh (Universitas Gadjah Mada, 2026)
The objective of the research was to evaluate the effectiveness of Faujasite zeolite-X, produced from coal fly ash, in removing methylene blue dye. The zeolite was synthesized using hydrothermal treatment, and its properties were analyzed using X-ray diffraction (XRD), scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM+EDAX), and Fourier-transform infrared spectroscopy (FTIR). Response surface methodology (RSM), employing a central composite design (CCD) was used to optimize the adsorption parameters. High-resolution XRD confirmed phase-pure, highly crystalline Faujasite zeolite-X, responsible for its superior adsorption ability. SEM shows conversion of amorphous coal fly ash to strongly crystalline Faujasite-type zeolite-X with sharp angular morphologies, confirming the process’s efficacy and its suitability for industrial use. Elimination of MB onto the synthesized adsorbent reached 99.23% at pH 9, contact time of 40 min at 55 °C, sorbent mass of 2.5 g/L, and an original dye concentration of 125 ppm. Unlike previous studies, this work integrates waste valorization with advanced statistical optimization to achieve superior dye removal efficiency. The optimized process not only develops the dye removal efficiency but also offers a green, scalable solution for coal fly ash utilization and textile sewage treatment, thereby addressing serious environmental issues and encouraging cleaner industrial performance.